Pregnancy Galectinology: Insights Into a Complex Network of Glycan Binding Proteins - Blois, Sandra M.; Dveksler, Gabriela; Vasta, Gerardo R.; Freitag, Nancy; Blanchard, Véronique; Barrientos, Gabriela (Frontiers in Immunology, 2019)
Galectins are a phylogenetically conserved family of soluble β-galactoside binding proteins, consisting of 15 different types, each with a specific function. Galectins contribute to placentation by regulating trophoblast development, migration and invasion - during early pregnancy. In addition, galectins are critical players regulating maternal immune tolerance to the embedded embryo. Recently, the role of galectins in angiogenesis during decidualisation and in placenta formation has gained attention. Altered expression of galectins is associated with abnormal pregnancies and infertility. This review focuses on the role of galectins in pregnancy-associated processes and discusses the relevance of galectin-glycan interactions as potential therapeutic targets in pregnancy disorders.